Dauerhafter Beton - Richtige Nachbehandlung 17. Symposium Baustoffe und Bauwerkserhaltung, Karlsruher Institut für Technologie (KIT), 11. März 2021 - Nolting, Ulrich; Dehn, Frank; Mercedes Kind, Vanessa (KIT Scientific Publishing, 2021)
Proper curing of concrete has a significant influence on its quality and properties. It is essential for both the strength development of the young concrete and its resistance to external impacts. The present conference proceedings provide an overview of the different methods of suitable curing and use inspirable practical examples to show how the increasing requirements can be met in the various areas of concrete construction.